PERANAN DISIPLIN KERJA DALAM MENINGKATKAN KINERJA PEGAWAI BAGIAN LAPANGAN UPTD TERMINAL KM 6 BANJARMASIN PADA DINAS PERHUBUNGAN PROVINSI KALIMANTAN SELATAN - Sri Mulyani; Majidan Noor (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2019)
Abstract, The purpose of this research was to determine the role of work discipline in improving employee performance in the UPTD field section of Terminal KM 6 Banjarmasin at the Department of Transportation of South Kalimantan Province. The method used in this research is descriptive method. This research which is the subject is all employees of the UPTD field in Terminal Km 6 Banjarmasin, amounting to 25 people. The results of the study show that the Work Discipline of UPTD Employees in Banjarmasin Km 6 at the Transportation Service of South Kalimantan Province is still low, there are employees who are late to work, waste time in working out of office during working hours, and a culture of procrastination. There was an undisciplined employee in wearing uniforms according to his schedule. The cause of work discipline is still low because of lack of optimal supervision and the failure to run sanctions against employees who are guilty or violate rules and regulations. The role of work discipline in improving employee performance in the field, namely by improving the function of supervision and sanctions. In addition, in an effort to reduce, reduce or even eliminate the occurrence of disciplinary violations by civil servants, the strategy to achieve successful implementation of civil servant discipline includes increasing the development of civil servants, increasing organizational support, increasing leadership commitment, strengthening the work ethic and increasing expectations.